Research on Power-Frequency Overvoltages of 220 kV Offshore Cable Transmission System in Liaoning Province. Issue 1 (1st February 2023) - Duan, Wei; Gu, Borui; Kong, Minru; Li, Han; Pu, Lu; Zhao, Xuefeng; Ju, Zeli
Abstract: Since power-frequency overvoltages can influence the safe operation of the submarine cable transmission system greatly, it is indispensable to calculate the overvoltages that may occur during actual situations. In this study, the power-frequency overvoltages of the offshore oil-gas field group's submarine cable transmission system are calculated through PSCAD/EMTDC. Among the different conditions considered, the maximum power-frequency overvoltage is 1.134p.u., which occurs in the case of single-phase fault earthing at the cable joint in L4. The result fulfills the limit of relevant regulations for the 220 kV transmission system, indicating that the submarine cable transmission system can operate safely and effectively, which can provide important guiding significance for the construction and operation of the system.